2017
DOI: 10.14814/phy2.13393
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the “Splenocardiac Axis” by electronic and tobacco cigarettes in otherwise healthy young adults

Abstract: The “Splenocardiac Axis” describes an inflammatory signaling network underlying acute cardiac ischemia, characterized by sympathetic nerve stimulation of hematopoietic tissues, such as the bone marrow and spleen, which then release proinflammatory monocytes that populate atherosclerotic plaques, thereby promoting ischemic heart disease. Electronic (e) cigarettes, like tobacco cigarettes trigger sympathetic nerve activation, but virtually nothing is known about their influence on hematopoietic and vascular tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…There are conflicting reports as to whether e-cigarette use is associated with cardiovascular disease in population studies 60,61 . Although a very small study in humans (n=9) suggested that e-cigarette use does not affect the metabolic activity of aortic wall tissue 62 , another showed that e-cigarette use increased arterial stiffness 63 . Murine models have shown that e-cigarette exposure leads to increased aorta stiffness and constrictor responses 64 , increased angiogenesis in heart tissue 65 , increased endothelial cell markers 63 and decreased vasodilation 64 .…”
Section: Clinical Analysis Of Cardio-respiratory Changesmentioning
confidence: 97%
“…There are conflicting reports as to whether e-cigarette use is associated with cardiovascular disease in population studies 60,61 . Although a very small study in humans (n=9) suggested that e-cigarette use does not affect the metabolic activity of aortic wall tissue 62 , another showed that e-cigarette use increased arterial stiffness 63 . Murine models have shown that e-cigarette exposure leads to increased aorta stiffness and constrictor responses 64 , increased angiogenesis in heart tissue 65 , increased endothelial cell markers 63 and decreased vasodilation 64 .…”
Section: Clinical Analysis Of Cardio-respiratory Changesmentioning
confidence: 97%
“…Oxidative stress develops following direct action of toxic compounds on the airways and alveolar epithelial cells [71]. Moreover, e-liquid decreases antioxidant activity [72]. Neutrophils and macrophages are probably the largest source of reactive oxygen species.…”
Section: Direct and Indirect Influence On Airway And Alveolar Epitheliummentioning
confidence: 99%
“…Similarly to smoke, e-cigarettes have elevated nicotine-depending blood presure and heart rate in acute observational or experimental studies [87]. Some authors have postulated activation of sympathetic central outflow as a part of "splenocardiac axis" [72]. However, the influence of these cardiac parameters is weaker than acute smoke exposure [87].…”
Section: Cardiovascular Effects Of E-cigarettesmentioning
confidence: 99%
“…Magas vérnyomásos dohányosokon e-cigarettára váltás után 12 hónapos követéssel mind a szisztolés, mind a diasztolés vérnyomás kisebb lett [40]. FDG-PET/CT szerint a nem dohányzókhoz viszonyítva e-cigaretta-használókon magasabb volt a lép és az aorta FDG-felvétele, de még magasabbnak bizonyult hagyományos cigarettát szívóknál [49]. Adatbázist feldolgozva a soha nem dohányzókhoz viszonyítva mindennapos e-cigaretta-használat esetén a szívinfarktus-rizikó hányadosa 2,25, mindennapos dohányzás esetén 2,95 [50].…”
Section: Légzőszerviunclassified